Case report: Point of care ultrasound as a diagnostic tool for orbital cellulitis - Rachna Subramony; Jeffrey Hendel; Jason Mallett (JEM Reports, 2023)
Background: Orbital cellulitis is a potentially life-threatening infection of the soft tissues surrounding the eye. Prompt diagnosis and treatment is crucial in mitigating damage to the delicate structures of the globe and orbit. Appropriate imaging is a key diagnostic tool and useful in differentiating from less severe infections such as preseptal cellulitis. Case: A 72 year old male with medical history notable for hypertension, hypothyroidism, and recently diagnosed multiple myeloma presented to the emergency department due to 3 days of right eye pain with associated swelling, erythema, and discharge. Point of Care Ultrasound (POCUS) performed in the Emergency Department was notable for peri-ocular fluid collection and edema, increasing suspicion for orbital cellulitis. Given the ultrasound findings, the patient was given intravenous antibiotics and was expedited for a contrast enhanced computed tomography (CT) scan of the orbit which demonstrated extraconal and intraconal fat stranding, confirming the diagnosis. The patient was treated with IV antibiotics and steroids and was discharged after an 11-day hospital admission with instructions to complete a 14-day course of antibiotics and 15-day taper of oral steroids. Why should an emergency physician be aware of this: To improve treatment outcomes and decrease the risk of vision loss, orbital cellulitis must be quickly diagnosed. A CT scan of the orbits is currently the gold standard in diagnosis, though in resource limited environments this imaging modality may not be readily available. Here, we present a typical case of orbital cellulitis in which POCUS was a useful tool in narrowing the diagnosis and ensuring prompt management of the infection.